Coping strategies as predictors of non-suicidal self-injury (NSSI) tendencies among university students - Shela Widi Cantika; Woro Apriliana Sari (Jurnal Psikologi Pendidikan dan Konseling: Jurnal Kajian Psikologi Pendidikan dan Bimbingan Konseling, 2026)
This study aims to examine the effect of coping strategies on Non-Suicidal Self-Injury (NSSI) behavior among students at Universitas Negeri Semarang. This study employed a quantitative design involving 125 respondents selected through purposive sampling. The research instruments used were the Brief COPE Scale and the Inventory of Statements About Self-Injury (ISAS). The data were analyzed using multiple linear regression. The results showed that, simultaneously, coping strategies had a significant effect on NSSI behavior (R² = 0,124; F = 5,692; p = 0,001). Coping strategies accounted for 12,4% of NSSI behavior, while the remaining 87,6% was influenced by factors outside the research model. Partially, the coping dimensions did not show a significant individual effect (p > 0,05). These findings indicate that the effect of coping strategies on NSSI behavior is collective, with statistical significance emerging from the interaction among coping dimensions as a whole rather than from the independent effect of each dimension. The implication of this study is the need for holistic intervention programs to optimize students’ overall coping systems as a preventive measure against NSSI.